DANGKE: SPECIFIC CULINARY ENREKANG SOCIETY - Masgaba, Masgaba (Kementerian Pendidikan dan Kebudayaan, 2021)
This study aimed to describe the processing methods and cultural values contained in the business of making Dangke. This study used descriptive qualitative methods with data collection techniques through interviews, observation, and literature study. The study result showed that Dangke is a kind of Enrekang people’s culinary. Initially, buffalo milk was the main ingredient used in making dangke, but it is replaced with milk from dairy cows today, because of the population of buffalo has decreased. The process of making Dangke used simple technology. Dangke was made using a coconut shell, thus its shaped like a dome, then packed using banana leaves. The values contained in the business of making Dangke were the cultural, social, economic, cooperation, accuracy, and used-effort values.